Microstructural properties of SiC based hardfacing on low alloy steel - Buytoz, S (Elsevier Science Sa, 2006)
The effects of tungsten inert gas arc-processing (TIG) parameters on the microstructure and microhardness of silicon carbide coatings were investigated experimentally. Coatings were developed with TIG processing on an SAE 1020 steel substrate. Depending on the processing parameters (e.g., heat input, powder content, and processing speed), silicon carbide particles completely dissolved during the processing and different microstructures were produced. At lower powder contents, the microstructures consisted of dendrites. However, at high powder contents, the microstructures consisted of M7C3 primary carbides, Fe3Si, SiC, and the graphitic carbon precipitates were generated. The microhardness of the surface layer was measured as a function of process parameters. Microhardness of the surface layer was significantly improved to as high as 1135 H-v as compared to 220 H-v of the substrate. The highest hardness measured 1250 H-v, which produced high heat input and low powder contents of 2.310 kJ mm(-1) and 1.5 g, respectively. The lower hardness of dendritic microstructure was related to the presence of primary dendrites and relatively low concentrations of Si and C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: cladding; dendrite; solidified mechanism; silicon carbide